A consultation-level intervention to improve care of frequently attending patients: a cluster randomised controlled feasibility trial. Issue 1 (2019) - Barnes, Rebecca K; Cramer, Helen; Thomas, Clare; Sanderson, Emily; Hollinghurst, Sandra; Metcalfe, Chris; Jackson, Sue; Record, Charlie; Thorley, Helen; Kessler, David
No abstract available